Characterization of two carbon allotropes, cyclicgraphene and graphenylene, as semi-permeable materials for membranes - Babicheva, Rita I. (2022)
Two-dimensional carbon-based structures have great potential in water purification. Density functional theory calculations and molecular dynamics simulations are performed to characterize two sp2-carbon allotropes, cyclicgraphene (Gr1) and graphenylene (Gr2), as semi-permeable materials for membranes. The allotropes demonstrate perfect salt rejection and good water flux, which, at the considered desalination conditions, are defined by the size of pores, their pore density per membrane unit area, as well as the interaction of particles with membranes. The paper discusses the differences between Gr1 and Gr2 having equilibrium structure and those subjected to 5% biaxial stretching. Gr1 has both higher water flux and strength to failure during biaxial tension than the denser Gr2. Such mechanical behaviour is due to a more uniform elongation of Gr1 interatomic bonds compared to Gr2. The use of these carbon allotropes for water treatment could be a less costly alternative to the application of graphene materials having the size of intrinsic pores insufficient for water molecule penetration.